2017
DOI: 10.1007/s10616-017-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin synergistically enhances antitumor activity of cisplatin in gallbladder cancer via the PI3K/AKT/ERK pathway

Abstract: Metformin (Met) is a widely used antidiabetic drug and has demonstrated interesting anticancer effects in various cancer models, alone or in combination with chemotherapeutic drugs. The aim of the present study is to investigate the synergistic effect of Met with cisplatin (Cis) on the tumor growth inhibition of gallbladder cancer cells (GBC-SD and SGC-996) and explore the underlying mechanism. Cells were treated with Met and/or Cis and subjected to cell viability, colony formation, apoptosis, cell cycle, west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In our study, we found that matrine could also arrest the cell cycle of EJ and T24 cells at G1 phase, while cisplatin increased primarily the S phase cell percentage in comparison with the untreated cells, which was consistent with many other researchers’ findings [ 19 ]. However, Bi’s research found that in gallbladder cancer a proportion of cells at the G1 phase increased compared with that of the control when treated with cisplatin [ 20 ]. The effect of cisplatin on the cell cycle distribution is still controversial, and remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that matrine could also arrest the cell cycle of EJ and T24 cells at G1 phase, while cisplatin increased primarily the S phase cell percentage in comparison with the untreated cells, which was consistent with many other researchers’ findings [ 19 ]. However, Bi’s research found that in gallbladder cancer a proportion of cells at the G1 phase increased compared with that of the control when treated with cisplatin [ 20 ]. The effect of cisplatin on the cell cycle distribution is still controversial, and remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these compounds increased the expression of p27, a cyclin-dependent kinase inhibitor ( Figure 4 E). In a previous report, the phosphorylation of ERK1/2 and Akt increased the expression of cyclinD1 and decreased the expression of p27 [ 31 , 32 , 33 ]. These results indicate that the antitumour effect of both astaxanthin and adonixanthin may be mediated by not cell death but cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Pris is a potential anticancer drug that can induce apoptosis in pancreatic cancer cells and colorectal cancer cells (15,41). Bi et al (42) reported that metformin synergistically enhances Cis-induced apoptosis via increasing the inhibition of Akt activity mediated by cisplatin. Liao et al (43) also revealed that matrine enhances the pro-apoptotic ability of Cis in urothelial bladder cancer cells through increasing the inhibition of Akt activity mediated by Cis (43).…”
Section: Discussionmentioning
confidence: 99%